2001
DOI: 10.1007/s11906-001-0094-7
|View full text |Cite
|
Sign up to set email alerts
|

Central sympathoinhibitory effects of calcium channel blockers

Abstract: It is generally assumed that the arterial vasodilation induced by inhibition of Ca(2+) influx into vascular smooth muscle cells represents the main mechanism for the hypotensive effect of dihydropyridine calcium channel blockers. Increases in sympathetic tone have been related to activation of the arterial baroreflex by rapid lowering of blood pressure. This review highlights new findings in two areas. First, in animal studies, direct central administration of dihydropyridines such as nifedipine or amlodipine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…45,46) It has also been shown that baroreflex sensitivity was increased significantly by chronic treatment with a Ca antagonist in patients with hypertension 47) and some Ca antagonists inhibited sympathetic nerve activity. 48,49) Therefore, in patients with stable effort angina and with impaired BRS, the same mechanisms might be observed with an ACE inhibitor or a Ca antagonist. These medications might alter the effect of cigarette smoking.…”
Section: Discussionmentioning
confidence: 89%
“…45,46) It has also been shown that baroreflex sensitivity was increased significantly by chronic treatment with a Ca antagonist in patients with hypertension 47) and some Ca antagonists inhibited sympathetic nerve activity. 48,49) Therefore, in patients with stable effort angina and with impaired BRS, the same mechanisms might be observed with an ACE inhibitor or a Ca antagonist. These medications might alter the effect of cigarette smoking.…”
Section: Discussionmentioning
confidence: 89%
“…Dihydropyridine CCBs have been shown to cause reflex sympathetic stimulation and tachycardia in association with a decrease in blood pressure (4,21), and this increased cardiac workload has been considered responsible for their limited preventive effects against cardiac complications (2,3). However, recent clinical studies indicated that tachycardia was not associated with the antihypertensive effects of azelnidipine, a new lipophilic dihydropyridine CCB (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been revealed that nifedipine, a short-acting dihydropyridine CCB, increases the risks of ischemic heart disease (2,3), a phenomenon that is thought to be mainly related to its reflex responses, i.e., activation of the sympathetic nervous system and tachycardia after rapid lowering of blood pressure (4). Therefore, the use of long-acting dihydropyridine CCBs is generally recommended in hypertensive patients (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Atorvastatin also reduces oxidative stress in the RVLM of SHRSP (62,63,64). With regard to the central sympathoinhibitory effects of calcium channel blockers, lipophilic dihidropyridine calcium channel blockers, such as nifedipine, nisoldipine, and amlodipine, readily cross the blood-brain barrier, thereby presumably blocking brain L-type Ca 2ϩ channels leading to central sympathoinhibition (73). It is generally considered that an arterial baroreflex-mediated increase in sympathetic activity is responsible for the unfavorable effects of short-and strong-acting dihydropyridine calcium channel blockers; therefore, the intrinsic sympathoinhibitory effects of calcium channel blockers have been ignored.…”
Section: Sympathoinhibitory Effects Of Antihypertensive Drugs and Stamentioning
confidence: 99%